Indocyanine Green Nanoparticles: Are They Compelling for Cancer Treatment? - Sevieri, Marta; Silva, Filippo; Bonizzi, Arianna; Sitia, Leopoldo; Truffi, Marta; Mazzucchelli, Serena; Corsi, Fabio (Frontiers in Chemistry, 2020)
Indocyanine green (ICG) is a Food and Drug Administration-approved near-infrared fluorescent dye, employed as an imaging agent for different clinical applications due to its attractive physicochemical properties, high sensitivity and safety. However, free ICG suffers from some drawbacks such as relatively short circulation half-life, concentration-dependent aggregation and rapid clearance from the body, that would confine its feasible application in oncology. Here, we aim to discuss encapsulation of ICG within a nanoparticle formulation as a strategy to overcome some of its current limitations and to enlarge their possible applications in cancer diagnosis and treatment. Our purpose is to provide a short but exhaustive overview of clinical outcomes that these nanocomposites would provide, discussing opportunities, limitations and possible impacts with regard to the main clinical needs in oncology.